2021
DOI: 10.4236/aim.2021.116024
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on the Pyogenic Pathogens and Their Antibiotic Susceptibility Patterns along with the ES<i>β</i>L Production

Abstract: Pyogenic infections are caused by various pathogens leading to pus formation and that can be attributed due to a wound either through accident or during surgery leading to infection spread. There are pathogenic strains that are not uncommon in hospital settings like Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter etc., that are multidrug resistant (MDR) and are a cause of concern. The bacteriological profile in the pyogenic infections tends to be same but there is a vast dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Bakteri yang paling umum menginfeksi pus pada luka adalah Staphylococcus aureus dan bakteri Gram-negatif lainnya seperti Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter yang bersifat multidrug resisten (MDR) (Chakraborty et al, 2021). Untuk bakteri Staphylococcus aureus yang multidrugs resistance dikenal sebagai MRSA (Metisilin Resisten S. aureus) umumnya bakteri ini resisten terhadap antibiotik golongan betalaktam, kemudian dikenal juga Extended Betalactamase (ESBL) umumnya adalah bakteri Gram negatif.…”
Section: Pendahuluanunclassified
“…Bakteri yang paling umum menginfeksi pus pada luka adalah Staphylococcus aureus dan bakteri Gram-negatif lainnya seperti Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter yang bersifat multidrug resisten (MDR) (Chakraborty et al, 2021). Untuk bakteri Staphylococcus aureus yang multidrugs resistance dikenal sebagai MRSA (Metisilin Resisten S. aureus) umumnya bakteri ini resisten terhadap antibiotik golongan betalaktam, kemudian dikenal juga Extended Betalactamase (ESBL) umumnya adalah bakteri Gram negatif.…”
Section: Pendahuluanunclassified
“…The cause of MDR in microbes is due to the mutation factor and by the horizontal gene transfer (HGT) between and within the species [ 13 ]. It has been observed that there is a rapid and broadly increased dissemination of antimicrobial resistance genes through HGT, especially in Enterobacteriaceae family such as encoding β -lactamases that includes extended spectrum β -lactamases and the metallo- β -lactamases (ESBLs and MBLs, respectively) [ 14 , 15 ], and it is a serious matter of concern that has reached pandemic proportions in healthcare settings worldwide [ 16 , 17 ]. These β- lactamases acquired pathogens have evolved as MDR strains, thus limiting to help in treating the infectious diseases, and in worst cases, the bacterial resistance to carbapenems has left us with treatment options using older and more toxic drugs like colistin [ 18 ].…”
Section: Introductionmentioning
confidence: 99%